Effects of mind-body exercise on individuals with ADHD: a systematic review and meta-analysis - Peng, Jin; Wang, Weiran; Wang, Yiting; Hu, Fengting; Jia, Mingyuan (Frontiers in Psychiatry, 2024)
ObjectiveTo explore the effects of mind-body exercise (MBE) on ADHD through a systematic review and meta-analysis.MethodsAfter identifying relevant search keywords based on the study’s technical terminology, research articles were retrieved from five databases. Two researchers independently screened the results to select studies that met the inclusion criteria. A random-effects model was used to conduct a meta-analysis on the included studies.ResultsThe findings indicate that MBE interventions significantly improved attention in individuals with ADHD [SMD=-0.97, 95% CI (-1.56, -0.39), P < 0.05]. However, the meta-analysis found no evidence that MBE improved executive function, emotional issues, or hyperactivity/impulsivity in ADHD patients.ConclusionsMBE is beneficial for attention improvement in ADHD patients. However, further evidence is needed to support its efficacy as an adjunctive treatment for other symptoms.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42023447510.